Reinventing medieval liturgy in Victorian England Thomas Frederick Simmons and the Lay Folks' Mass Book - Jasper, David 1951-; Smith, J. J. 1955- (Medievalism, 2023)
In 1879, Canon Thomas Frederick Simmons edited the late medieval poem now known as 'The Lay Folks' Mass Book' creating what remains the standard edition of the text. This volume shows how Simmons' interest in the text was related profoundly to contemporary debates about worship in the Church of England, and how he used his medievalist researches as the basis for the most important attempt at Prayer Book revision between the Reformation and the twentieth century